2007
DOI: 10.1016/j.ijid.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among urinary tract Escherichia coli isolates from inpatients and outpatients in a tertiary care center in São Paulo, Brazil

Abstract: hallucinations is unusual for intoxication with atropine or scopolamine, but could be explained by delayed digestion of non-ground Jimson weed seeds. Postprandial 'inability to vomit', followed by unconsciousness and auditory hallucinations, as reported by this patient, clearly is consistent with tropane alkaloid poisoning, and, together with laboratory results (50 seeds D. stramonium/kg of grain), confirm contamination by Jimson weed to be the cause of this event. Foodborne disease outbreaks are recognized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
1
4
0
3
Order By: Relevance
“…The proportion of females (77.6% vs. 69%-88.8% in studies), the female-to-male ratio by age group, the age group most affected (15-64 years: 57.2%) and the first isolated agent ( E. coli , 70.2%) and frequency is very similar to that found in many published studies 2,4,9,10,15,19,20,25,26 . The percentage of E. coli that is isolated from UTIs, according to international literature, is 75% to 95% 15 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The proportion of females (77.6% vs. 69%-88.8% in studies), the female-to-male ratio by age group, the age group most affected (15-64 years: 57.2%) and the first isolated agent ( E. coli , 70.2%) and frequency is very similar to that found in many published studies 2,4,9,10,15,19,20,25,26 . The percentage of E. coli that is isolated from UTIs, according to international literature, is 75% to 95% 15 .…”
Section: Discussionsupporting
confidence: 83%
“…All studies of this type in Brazil, except for one 10 , are retrospective and exclude many demographic variables, except gender and age, as well as clinical, radiological or laboratory variables, which does not allow multivariate analysis, and thus, greatly reduces the impact of these publications 1,2,4,9,19,20,25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Fortaleza in the northeast of Brazil, a lower resistance rate of 7.5% was described for norfloxacin ( Araújo et al , 2011 ). In Europe, a multicentric study showed a ciprofloxacin resistance rate from 1.4% to 12.9% ( Schito et al , 2009 ), whereas a higher rate (31%) was registered in the hospitalized population in Ribeirão Preto, Brazil ( Santo et al. , 2006 ).…”
Section: Resultsmentioning
confidence: 99%